2017
DOI: 10.4172/neuropsychiatry.1000195
|View full text |Cite
|
Sign up to set email alerts
|

An adolescent case of limbic encephalitis with anti leucine-rich glioma inactivated 1 antibodies

Abstract: Background: Limbic encephalitis associated with leucine-rich glioma inactivated 1 (LGI1) antibodies can initially have either neurological or psychiatric manifestation. Subject and methods: The paper describes a case of a 14-year old girl with LGI1 antibodiesassociated limbic encephalitis with initial symptoms suggesting psychotic disturbances. Results: The magnetic resonance imaging (MRI) of the head was normal and the electroencephalography (EEG) presented low voltage with inter-hemispheric asymmetry and par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…LGI‐1 limbic encephalitis has been reported predominantly in adults with a mean age at onset of around 63 years (Li et al, 2018a). Janas‐Kozik et al reported a case of a 14‐year‐old adolescent girl with limbic encephalitis associated with LGI‐1 antibodies who presented with seizures, autonomic instability, and psychotic symptoms (Janas‐Kozik et al, 2017). To our knowledge, our patient is the youngest case ever reported in the literature and highlights the importance to consider this diagnosis also in children.…”
Section: Discussionmentioning
confidence: 99%
“…LGI‐1 limbic encephalitis has been reported predominantly in adults with a mean age at onset of around 63 years (Li et al, 2018a). Janas‐Kozik et al reported a case of a 14‐year‐old adolescent girl with limbic encephalitis associated with LGI‐1 antibodies who presented with seizures, autonomic instability, and psychotic symptoms (Janas‐Kozik et al, 2017). To our knowledge, our patient is the youngest case ever reported in the literature and highlights the importance to consider this diagnosis also in children.…”
Section: Discussionmentioning
confidence: 99%
“…These models effectively improve the screening of perinatal women for depression using the Patient Health Questionnaire (PHQ-2 or PHQ-9) in tertiary care settings 13 and can be included as community-based assessments (e.g., Community Based Assessment Checklist in India) and part of national programs. 14 However, there are various challenges for the implementation of these interventions/models in resource-limited settings, including limited training resources, overburdened primary HCWs with multiple responsibilities under different programs, and difficulty maintaining records and arranging follow-ups. Most of these issues, however, can be addressed by innovative technology-based interventions.…”
Section: Approaches To Reduce the Treatment Gapmentioning
confidence: 99%
“…Still, parts of some studies do not show any abnormalities, e.g., [56]. Some patients suffering from the initial phase of NMDAR autoimmune encephalitis with NR1 antibodies may exhibit schizophrenia-like psychotic behavior [60,61] or symptoms of hypofrontality [62], however, the vast majority of recent studies do not confirm the presence of IgG-NR1 antibodies in schizophrenia [63,64].…”
Section: Glutamatergic Signaling and Cognitive Deficits In Schizopmentioning
confidence: 99%